2011
DOI: 10.1097/ico.0b013e3181e84689
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Recurrent Corneal Erosion by Extended-wear Bandage Contact Lens

Abstract: Three-month BCL treatment is a safe and effective medical therapy with a relatively low recurrence rate of RCE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 13 publications
0
26
0
3
Order By: Relevance
“…[8][9][10][11][12] Silicone hydrogel contact lenses are particularly preferred in therapeutic indications because of their high oxygen permeability, and therefore, suitability for extended wear. Bandage contact lenses cover the exposed corneal nerve endings and protect the cornea from frictional forces of the lids providing immediate relief of pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12] Silicone hydrogel contact lenses are particularly preferred in therapeutic indications because of their high oxygen permeability, and therefore, suitability for extended wear. Bandage contact lenses cover the exposed corneal nerve endings and protect the cornea from frictional forces of the lids providing immediate relief of pain.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] The use of contact lenses in the setting of active ocular surface infection is generally contraindicated with the concern of exacerbation of the infectious process. However, adenoviral keratoconjunctivitis is a disabling ocular surface disease, which, even in the early stages, may be accompanied by corneal epithelial defects or filamentous keratopathy leading to severe pain and photophobia.…”
mentioning
confidence: 99%
“…They also discuss the difficulty in the timing of removal of the contact lens but advocate that the lens should be removed if the patient is symptom-free for 3 months. This recommendation was echoed by Fraunfelder and Cabezas, 46 who carried out a retrospective study of 12 patients with recurrent corneal erosions. They prescribed a bandage contact lens for 3 months, replaced every 2 weeks, and found that this produced a long-term resolution in most recalcitrant cases of recurrent corneal erosions.…”
Section: Therapeutic Contact Lensesmentioning
confidence: 99%
“…5 The majority of patients respond to medical management alone including the use of lubricating and antibiotic agents, cycloplegics, and bandage contact lenses. [2][3][4][5]10 However, recalcitrant cases often require adjunct surgical treatments that are more effective in promoting normal epithelial to stromal adhesion after debridement of all loose corneal epithelium. 5,9 Therapeutic modalities include diamond burr superficial keratectomy (DBSK), alcohol delamination, anterior stromal puncture, and phototherapeutic keratectomy.…”
mentioning
confidence: 99%